Evaluation of an Advisor Tool for Scenario Generation - Shin, Jae Eun; Sutcliffe, Alistair G.; Gregoriades, Andreas (My University, 2003)
This study investigates the usefulness of a scenario advisor tool which was designed to be used in the military domain where human or machine errors cause safety-critical problems. The tool provides traceability between scenario models and requirements and helps to generate new scenarios and scenario variations. Through two series of evaluation sessions, we found that the tool is useful to generate scenarios
Keywords: scenario generation; user evaluation; scenario schema; scenario taxonomy